Catalytic Transesterification Of Waste Cooking Oil Using Fe-modified Chicken Bone Catalyst: Characterization And Optimization - Nurul Izzati Saharuddin; Muhammad Afiq Danial Mohamed Nassir; Aina Zulaikha Muzafar Shah; Tengku Shafazila Tengku Saharuddin; Nurul Jannah Abd Rahman; Syahirah Yahya; Farah Wahida Harun (UKM, 2025)
Indexed by ISI and Scopus (Tier 2)